Analytic Continuation of Euler Polynomials and the Euler Zeta Function. (3rd April 2014) - Ryoo, C. S.
Abstract : We study that the Euler numbers E n and Euler polynomials E n z are analytically continued to E s and E ( s, w ) . We investigate the new concept of dynamics of the zeros of analytica continued polynomials. Finally, we observe an interesting phenomenon of "scattering" of the zeros of E ( s, w ) .